2010
DOI: 10.1007/s10646-010-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of sodium and potassium on the tropical freshwater cladoceran Pseudosida ramosa

Abstract: In this study, the toxicities of sodium and potassium to the tropical freshwater cladoceran Pseudosida ramosa were assessed. Acute toxicity tests on this species showed that the 48-h LC(50) of Na(+) was 556 mg l(-1), while that of K(+) was 17.7 mg l(-1). Long-term exposure of female P. ramosa to sodium reduced the total number of survivors from 10 to 6 at a concentration of 249 mg l(-1), 21-day fecundity from 20.4 to 14.3 eggs female(-1) at concentrations ranging from 72 to 249 mg l(-1), 21-day fertility from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…death and colonization (detrital quality (3)) consumption (13) c ( 6 ) e m e r g e n c e ( 7 ) u p ta k e ( 8 ) l i t t e r f a l l ( 9 ) Figure 1. Riparian -stream interactions that could be altered by salt additions.…”
Section: Predicted Detrital Alterations From Salinizationmentioning
confidence: 99%
“…death and colonization (detrital quality (3)) consumption (13) c ( 6 ) e m e r g e n c e ( 7 ) u p ta k e ( 8 ) l i t t e r f a l l ( 9 ) Figure 1. Riparian -stream interactions that could be altered by salt additions.…”
Section: Predicted Detrital Alterations From Salinizationmentioning
confidence: 99%
“…NaBr and 3,4-dichloroaniline (29), ibuprofen (30), and insecticides (31). An increased number of aborted eggs and a reduction in the number of hatched individuals have been documented in NaCl solutions at concentrations of Na ranging from 25 to 249 mg L -1 Na + and 41 to 249 mg L -1 Na + , respectively, in chronic exposure of the freshwater cladoceran Pseudosida ramosa (32,33). Baird et al (29) reported that the chronic inhibition of reproduction in D. magna at 3 to 17 mg L -1 NaBr was due solely to the acute lethal effect on eggs developing in the brood chamber.…”
Section: Resultsmentioning
confidence: 99%
“…However, in La Pampa, this species has been recorded in water bodies with a wide range of salinity of up to approximately 22 g.L -1 (Hammer 1986). Anthropic eutrophication, which is due to the input of an excess of nutrients (phosphorus and nitrogen) into any water body, can come from three sources: industrial, domestic or agricultural (Freitas & Rocha 2011). In other parts of the world, M. macrocopa is often associated with hypertrophic or eutrophic environments with high anthropogenic influence, especially those under the influence of cities; for example, sewage treatment basins or rivers with strong domestic organic pollution, such as the Mula River in India (Vanjare et al 2010), or those impacted by industrial activities, such as lakes for paper-making industry sewage treatment (Espinosa-Chávez et al 1992, Martínez & Gutiérrez 1997, Benider et al 1998.…”
Section: Discussionmentioning
confidence: 99%